VISUAL ANALYSIS PUPPET OF “SI UNYIL” FILM AS INDONESIAN CULTURAL IDENTITY - Mulyana, Agus Rahmat; Dewi, Agustina Kusuma; Setiawan, Sulistyo (International Journal of Humanity Studies (IJHS), 2023)
"Si Unyil" is a television series for Indonesian children, created by Suyadi and in production by the National Film Production Center (PPFN).  "Si Unyil" belongs to the hand puppets category, consisting of the head, body, and hands. The attraction of the film "Si Unyil" lies in the facial expressions of the doll called Wanda, and is supported by the strength of the story contains elements of humor, joy, tension, to sadness. This study uses a semiotic approach that focuses on the analysis of Wanda "Si Unyil", as the central character in the film "Si Unyil"; and several supporting characters in the film, i.e. Pak Raden, Pak Ogah, Cuplis, and Meilani. Wanda can represent certain facial characters for certain roles in certain storylines. Therefore, Wanda can carry comprehensive meanings that indicate emotional conditions, physical conditions, and environmental conditions. Analysis of "Si Unyil" through the visual of the puppet, concluded that "Si Unyil" contains educational values, morals, and social ethics that are displayed in various daily activities, through dialogue and the behavior between "Si Unyil" and his friends. "Si Unyil" film also possible to be a representation of the Indonesian people, which is guided by the ideology of Pancasila.